Application of a generalized additive mixed model in time series study of dairy cow behavior under hot summer conditions - C. Ferrari; C. Evangelista; L. Basiricò; S. Castellani; S. Biffani; U. Bernabucci (Journal of Dairy Science)
ABSTRACT: This study investigated the pattern of 6 behavioral parameters in Holstein dairy cows under heat stress (HS) conditions using a generalized additive mixed model (GAMM) statistical approach, while also evaluating the effectiveness of a commercial electrolyte, osmolyte, and antioxidant blend in mitigating HS-induced adverse effects. The trial was conducted during a severe Italian summer on 84 multiparous dairy cows in the Central Italy, divided into 4 balanced groups (2 treated and 2 control) of 21 cows each. All animals received the same diet, and the treatment groups were supplemented with 3,150 g/d of the additive. Behavioral parameters, namely low activity (LA), medium activity (MA), high activity (HA), rumination time (RUM), eating time (ET), and heavy breathing (OH), were monitored using neck collar sensors. Generalized additive mixed models were used to analyze trajectory changes of these parameters over time and climatic conditions. Results indicated significant variations in only one activity parameter, with treated cows showing increased MA with rising temperature-humidity index (THI). Eating time declined with increasing HS, particularly in the treated group, suggesting potential HS relief. Rumination time decreased with increasing HS levels but increased also with milk yield and lactation stage. As expected, heavy breathing significantly increased with THI, especially beyond THI 80, and was influenced by milk yield and lactation stage but not by the treatment. The use of GAMM enhanced visualization and understanding of severe climatic conditions' effects on behavioral parameters.